Laporan Kegiatan Sosialisasi Mahasiswa Magang Bawaslu Kota Banjarmasin (Sosialisasi Stop Bully : Jadilah Teman yang Baik) - Raudatun Nazwa; Annisa Hamdah; Alifya Zhafira; Mahdianoor; Febry Ananda Ridhoni; Nuril Khasyi’in (Interdisciplinary Explorations in Research Journal, 2024)
The "Stop Bully, Be a Good Friend" socialization event at PAUD Cahaya Ilmu aims to teach children the importance of kindness, respecting differences, and creating a safe environment. By involving parents and educators, this initiative focuses on fostering healthy social and emotional development for children. Bullying, whether physical or verbal, often arises from a lack of understanding about mutual respect. Early education is essential to prevent these negative behaviors. Through educational games, interactive stories, and group activities, children are encouraged to understand the values of friendship and empathy. This event aims to build collective awareness to prevent bullying, creating a positive and caring learning environment.